Assessment of fluid status in neonatal dialysis: the need for new tools - Nourbakhsh, Noureddin; Benador, Nadine (Pediatric nephrology (Berlin, West), 2023)
Background Assessment of fluid status in neonatal dialysis has largely focused on traditional tools including clinical assessment, serial weights, and blood pressure (BP) measurements. However, in infants on kidney replacement therapy, the assessment of fluid overload is problematic due to errors in weight assessment, subtlety of physical exam findings, and inaccuracy of non-invasive BP measurements. Case summary In this presentation of a neonate with bilateral renal agenesis requiring kidney replacement therapy, the treating team assessed a number of variables in determining the ultrafiltration prescription for dialysis across 2 modalities (hemodialysis and continuous kidney replacement therapy). Complications Fluid overload, cardiomegaly, and worsened respiratory status occurred when attempting to assess the neonate’s fluid status by traditional markers (weights, blood pressures, physical exam findings). B-type natriuretic peptide (BNP) was obtained and was noted to correlate with the degree of fluid overload. Key management points Compared to traditional tools for assessment of fluid status in pediatric dialysis, BNP assisted the medical team in optimizing the volume status of the subject and determining optimal daily ultrafiltration goals. Due to the rapid release in response to myocardial stretch and the lack of kidney clearance of the peptide, BNP may represent an objective, timely, and reliable index of volume status in the pediatric dialysis patient.